The environmental consequences of growth: Empirical evidence from the Republic of Kazakhstan - Amantay Akbota; Jungho Baek (Economies, 2018)
The main objective of this paper is to examine the effect growth has on CO2 emissions in Kazakhstan, controlling for energy consumption, in the autoregressive distributed lag (ARDL) cointegration framework. We find that the environmental Kuznets curve (EKC) hypothesis seems to hold for Kazakhstan; this effect at a low level of income increases CO2 but at a high level decreases it. We also find that energy consumption increases CO2 emissions.
Keywords: C2; Q4; Q5; 330; ARDL; CO2 emissions; environment; growth; Kazakhstan